2003
DOI: 10.1139/p03-004
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation by kerosene soot under upper tropospheric conditions

Abstract: Quasi-elastic neutron scattering (QENS) and neutron diffraction (ND) experiments were conducted to characterize the dynamics and structure of water/ice confined in a well-defined kerosene-soot pores network at 40, 60, and 100% relative humidity and at temperatures from 283 to 204 K. The QENS spectra indicate that about 35% of the adsorbed water is in an amorphous solid-like state at T = 283 K and that an appreciable amount of liquid water exists in the soot supermicropores down to the lowest temperature invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The morphology also presents a challenge. Quasi-elastic neutron-scattering studies of water on kerosene soot showed that water in a liquidlike state exists in pores of particles down to -73°C (Suzanne et al 2003). …”
Section: _1mentioning
confidence: 99%
“…The morphology also presents a challenge. Quasi-elastic neutron-scattering studies of water on kerosene soot showed that water in a liquidlike state exists in pores of particles down to -73°C (Suzanne et al 2003). …”
Section: _1mentioning
confidence: 99%
“…Owing to the fractal-like morphology of soot particles, it is possible that their ice nucleation efficiency may be affected by water-filled micropores even in water-subsaturated conditions due to a negative curvature effect (Suzanne et al, 2003). In this context, the formation of short-lived contrails (in a subsaturated atmosphere) may be of special relevance, because soot particles experience water supersaturations and the resulting droplets freeze when forming contrails (Kärcher et al, 1996).…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Such an indirect effect could in principle work whether or not a short-lived contrail is involved, but the involvement of a short-lived contrail could enhance the effect because of preactivation. Preactivation means that tiny amounts of ice remain in the cracks and pores of soot particles after evaporation of the contrail [18]. These tiny ice remainders can act as good ice nuclei in the later fate of the particles.…”
Section: Contrails and Contrail Cirrus In The Atmosphere And Their Pmentioning
confidence: 99%